Hinkelammert's contribution to critic thought - Mora Rodríguez, Arnoldo (2025)
Without intending to fully develop the philosophical foundations of Franz Hinkelammert's invaluable contribution to Latin American critical thought, I will outline in the following lines some of his fundamental ideas as a posthumous tribute.